2022
DOI: 10.1002/anie.202212273
|View full text |Cite
|
Sign up to set email alerts
|

Dual Activation of Molecular Oxygen and Surface Lattice Oxygen in Single Atom Cu1/TiO2 Catalyst for CO Oxidation

Abstract: The in-depth mechanism on the simultaneous activation of O 2 and surface lattice O 2À on one active metallic site has not been elucidated yet. Herein, we report a strategy for the construction of abundant oxygen activation sites by rational design of Cu 1 /TiO 2 single atom catalysts (SACs). The charge transfer between isolated Cu and TiO 2 support generates abundant Cu I and 2-coordinated O lat sites in Cu 1 À OÀ Ti hybridization structure, which facilitates the chemisorption and activation of O 2 molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In the presence of gaseous oxygen, the contribution of O latt needs to be considered in a comprehensive manner. The abundance of oxygen vacancies over SMO–CaO after the active O latt consumption provided numerous sites for the activation of adsorbed oxygen, which took a driving role in the ignition stage of catalytic combustion. Thus, the addition of gaseous oxygen significantly reduced the temperature at which CO 2 started to form over SMO–CaO (93 °C) compared with that on SMO–SiO 2 (150 °C) (Figure b). Meanwhile, more active O latt imparted by interface interaction enabled the complete conversion of chlorobenzene at 260 °C over SMO–CaO and up to 360 °C over SMO–SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of gaseous oxygen, the contribution of O latt needs to be considered in a comprehensive manner. The abundance of oxygen vacancies over SMO–CaO after the active O latt consumption provided numerous sites for the activation of adsorbed oxygen, which took a driving role in the ignition stage of catalytic combustion. Thus, the addition of gaseous oxygen significantly reduced the temperature at which CO 2 started to form over SMO–CaO (93 °C) compared with that on SMO–SiO 2 (150 °C) (Figure b). Meanwhile, more active O latt imparted by interface interaction enabled the complete conversion of chlorobenzene at 260 °C over SMO–CaO and up to 360 °C over SMO–SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the C 3 H 8 -TPSR with or without adding water is explored to study the surface reactive oxygen species (Figure d). It can be observed that surface lattice oxygen (200–450 °C) is the main reactive oxygen species for propane oxidation, further showing that this reaction follows the MvK mechanism. The reaction temperature of surface lattice oxygen over Co 3 O 4 -S and Co 3 O 4 -P in the presence of water is markedly higher than that in the absence of water.…”
Section: Resultsmentioning
confidence: 99%
“…The engineering of the first or higher coordination shells by precisely tailoring the heterogeneity of coordination atoms offers a great opportunity to tune the properties of SACs. [194][195][196][197][198][199][200][201][202] Compared to engineering the first coordination shell, engineering the second and/or higher coordination shells would alter the distribution of the electron density over the central single metal sites indirectly and more moderately through long-range electron delocalization, thus tuning the catalytic performance of SACs. 181 The effects of engineering the coordination shell is not just to redistribute uneven charge and thus optimize the adsorption energies of intermediate species, but also to modify the conductivity of the supported framework and thus improve charge conduction.…”
Section: Coordination Atomsmentioning
confidence: 99%